LANFO with Recycled Oil Practical and Economic Advantages - A J. Rorke; U Chhika (International Society of Explosives Engineers, 1995)
"A series of tests was carried out on a dry blend of PPAN and LAN prills (LANFO). The objective of thetests was to determine detonation stability and VOD performance compared to ANFO. Heave andfragmentation results in the field were also evaluated visually. A number of factors were behind for.mulating this blend. A lower cost is combined with higher in-hole energies, but at slower reactionrates and lower peak borehole pressures. The resultant effect is improved heave characteristics andlower energy losses caused by inefficient crushing of the rock immediately around the borehole.The test results indicate that IANFO is ideally suited to blasting in softer midburden and overburdenrock types often encountered in coal strip mines."